2021
DOI: 10.1177/21501327211024400
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines: Discharge Instructions for Covid-19 Patients

Abstract: Introduction/Objectives: Clinicians treating COVID-19 patients face a major challenge in providing an effective relationship with patients who are discharged to return to home in order to optimize patient self-management after discharge. The purpose of these discharge instructions is to assist and provide guidance for physicians, nurses, and other health care personnel involved in discharging COVID-19 patients to home after encounters at hospitals, emergency departments, urgent care settings, and medical offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 94 publications
1
10
0
4
Order By: Relevance
“…Patients in this study suggested that there be follow‐up calls from either family doctors notified of their patients' COVID‐19 status or from AHS staff (e.g., discharging hospital transition coordinators). This aligns with other studies clearly indicating the need for regular monitoring of discharged patients to assess clinical status as well as the need for medical or rehabilitation care 12–15 . Approaches for follow‐up with those patients having other medical conditions were different.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Patients in this study suggested that there be follow‐up calls from either family doctors notified of their patients' COVID‐19 status or from AHS staff (e.g., discharging hospital transition coordinators). This aligns with other studies clearly indicating the need for regular monitoring of discharged patients to assess clinical status as well as the need for medical or rehabilitation care 12–15 . Approaches for follow‐up with those patients having other medical conditions were different.…”
Section: Discussionsupporting
confidence: 84%
“…This aligns with other studies clearly indicating the need for regular monitoring of discharged patients to assess clinical status as well as the need for medical or rehabilitation care. 12 , 13 , 14 , 15 Approaches for follow‐up with those patients having other medical conditions were different. They had virtual care and monitoring by their family doctors or specialty healthcare teams including ongoing assessment of their COVID‐19 status and additional supports or treatment as needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations